Credibility, Pre-Production and Inviting Competition in a Network Market - Amir Etziony; Avi Weiss (Bar-Ilan University, Department of Economics, 2002)
In this paper we considered a new solution to the credibility problem present in network industries. This problem arises because the value of a network good to its owner depends positively on the number of consumers who buy the good. Because of this property, it is in the interest of the producer to try to convince consumers that the market will be large, even if he knows it is untrue. Consumers, in turn, will disregard producer claims, and will, instead, try to reason out what size the market will attain. As a result, a lower than optimal quantity, both for consumers and producers, will be produced, i.e., the resulting equilibrium is Pareto inefficient. Katz and Shapiro (1985) and Economides (1996) suggest a solution to this problem in which the firm invites competitors to share their technology and enter the market, thus voluntarily giving up their monopoly position. We suggest an alternative remedy of pre-producing the good. This has the effect of changing the firm's cost structure in a manner that causes consumers to believe that the amount they will optimally sell (and hence the market size) will increase, again leading to higher profitability. The two strategies are compared, and we show the conditions under which each is preferable. We then consider combinations of these two strategies in two different manners. In the first the leader produces and then invites competitors who then also pre-produce, and in the second the leader pre-produces but the fringe firms do not; rather, they produce in the same period in which they sell. Surprisingly we found that the latter dominated the former, which led us to a better understanding about how and why each strategy works. In short, inviting competitors creates a positive externality that benefits all firms, while pre-producing helps only the firm doing the pre-producing and harms all other firms. Thus, the leader invites competitors so he can benefit from the positive externality, but he is better off if the competitors do not pre-produce.
Keywords: D21; D43; 330; Network market; pre-production; inviting competition; network externalities